Does cigarette smoking exacerbate the effect of total cholesterol and high-density lipoprotein cholesterol on the risk of cardiovascular diseases?. Issue 11 (5th February 2009) - Nakamura, K; Barzi, F; Huxley, R; Lam, T-H; Suh, I; Woo, J; Kim, H C; Feigin, V L; Gu, D; Woodward, M; ,
Abstract : Objective: To explore whether an interaction between smoking and serum total cholesterol (TC) and/or decreased levels of serum high-density lipoprotein cholesterol (HDLC) exists for any major subtype of cardiovascular disease. Design: An individual participant overview of 34 cohort studies. Setting: The Asia-Pacific region. Participants: People aged ⩾20 years without a particular condition or risk factor. Mean outcome measures: Hazard ratios (HRs) and 95% confidence intervals (CIs) for both TC and HDLC by smoking status were estimated using Cox proportional hazard models adjusted for age and systolic blood pressure and stratified by study and sex. Results: During follow-up (median 4.0 years), 3298 coronary heart disease (CHD) and 4318 stroke events were recorded. For CHD, the HR (95% CI) for an additional 1.06 mmol/l increment in TC was greater in current smokers than in non-smokers: 1.54 (1.43 to 1.66) versus 1.38 (1.30 to 1.47); p = 0.02. Similarly, the HR (95% CI) for an additional 0.40 mmol/l decrement in HDLC was greater in current smokers than in non-smokers: 1.67 (1.35 to 2.07) versus 1.28 (1.10 to 1.49); p = 0.04. The positive association of TC with ischaemic stroke, and the negative association of TC with haemorrhagic stroke, were broadly similar for current smokers and non-smokers. Similarly, the risks of both the subtypes of stroke remained broadly unchanged as HDLC decreased in both current smokers and non-smokers. Conclusions: Smoking exacerbated the effects of both TC and HDLC on CHD, although no interaction between smoking and TC or HDLC existed for either of the subtypes of stroke.